2020
DOI: 10.5336/nurses.2020-74985
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Patients' Perceptions of Nursing Care Quality and Their Satisfactions with Nursing Care

Abstract: Sağlık hizmetlerindeki gelişmeler, hasta hakları bilincinin yaygınlaşması, toplumun hizmet beklentilerinin artması gibi pek çok faktör, verilen hizmeti eleştiren ve bakımlarında daha aktif konuma gelen bireylerin ortaya çıkmasına yol açmıştır. 1,2 Bu değişimler sağlık hizmeti sunucularını hizmet kalitesini değerlendirme ve iyileştirme zorunluluğuyla karşı karşıya getirmiştir. Günümüzde sağlık hizmetlerinin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…This finding is consistent with other studies in the literature. Gürkan et al (2020) and Kersu et al (2020) observed surgical patients’ satisfaction with postoperative nursing care at a good level. Yeşilyaprak et al (2019) found that the satisfaction of patients who underwent organ transplantation was at a good level, and a good level of satisfaction was also observed in urology patients by Yanmış (2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding is consistent with other studies in the literature. Gürkan et al (2020) and Kersu et al (2020) observed surgical patients’ satisfaction with postoperative nursing care at a good level. Yeşilyaprak et al (2019) found that the satisfaction of patients who underwent organ transplantation was at a good level, and a good level of satisfaction was also observed in urology patients by Yanmış (2018).…”
Section: Discussionmentioning
confidence: 97%
“…The sample included patients in general surgical and medical clinics in the study of the Turkish adaptation of the scale (Uzun 2003). The Turkish version of the scale is a valid and reliable measurement tool, and it is widely used in study conducted with surgical patients in Turkey (Arslan & Gürsoy 2021, Gürkan et al 2020, Kersu et al 2020, Yeşilyaprak et al 2019). In the Turkish adaptation of the scale, Cronbach’s alpha value was determined to be 0.94 (Uzun 2003).…”
Section: Instrumentsmentioning
confidence: 99%
“…These experiences can render patients more vigilant and informed, elevating their expectations and sensitivity toward the services they receive. [40,41] This outcome could potentially be linked to factors such as the nature of patients' prior hospitalizations or surgeries, the extent to which their preoperative physiological and psychological needs were addressed, and the caliber of nursing care they received during their postoperative phase, despite these aspects not being directly inquired about within this study.…”
Section: Discussionmentioning
confidence: 99%
“…İncelenen literatür çalışmalarında, bizim çalışmamızla paralel olarak hemşirelerin "BDÖ-24" düzeylerinin yüksek olduğu, en düşük düzeyde ''bağlılık'', en yüksek düzeyde ise ''bilgi beceri'' puanlarının olduğu belirlenmiştir. 17,18,[25][26][27][28][29] Çalışmamızdaki bu durumun hemşirelerin çoğunun yükseköğretim mezunu, katılımcıların yaş ortalamaları, büyük çoğunluğunun çalışma yıllarının az olması ve servis hemşiresi olmalarından kaynaklandığı düşünülmektedir.…”
Section: Buunclassified